2018
DOI: 10.1186/s12918-018-0662-y
|View full text |Cite
|
Sign up to set email alerts
|

Integrating node embeddings and biological annotations for genes to predict disease-gene associations

Abstract: BackgroundPredicting disease causative genes (or simply, disease genes) has played critical roles in understanding the genetic basis of human diseases and further providing disease treatment guidelines. While various computational methods have been proposed for disease gene prediction, with the recent increasing availability of biological information for genes, it is highly motivated to leverage these valuable data sources and extract useful information for accurately predicting disease genes.ResultsWe present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…Akin to LP [38,75,76] , node embeddings also offer a convenient route to incorporating multiple networks into SL approaches. While methods such as SL-I and SL-A may require concatenating the original networks or integrating them into a single network before learning, recent work has shown that SL-E-based methods can embed information from multiple molecular/heterogeneous networks and learn gene classifiers in tandem [77][78][79][80][81][82][83][84][85] . However, none of these studies have compared the variety of SL-E methods to learning directly on the adjacency matrix.…”
Section: Discussionmentioning
confidence: 99%
“…Akin to LP [38,75,76] , node embeddings also offer a convenient route to incorporating multiple networks into SL approaches. While methods such as SL-I and SL-A may require concatenating the original networks or integrating them into a single network before learning, recent work has shown that SL-E-based methods can embed information from multiple molecular/heterogeneous networks and learn gene classifiers in tandem [77][78][79][80][81][82][83][84][85] . However, none of these studies have compared the variety of SL-E methods to learning directly on the adjacency matrix.…”
Section: Discussionmentioning
confidence: 99%
“…Many use graph-based methods, the most widely used being diffusion or random walk algorithms [ 12 , 13 , 14 , 15 , 16 , 17 ]. Other graph-based approaches include N2VKO [ 18 ], using node embeddings based on node2vec [ 19 ], CIPHER [ 20 ], based on gene network closeness and phenotype similarity, a gene gravity-like algorithm [ 21 ], and deep learning [ 22 ]. Other approaches not based on graphs include machine learning algorithms trained on functional similarity [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…To build this model they derived gene-gene mutual information from known gene-disease association data and then combined them with known protein-protein interaction networks using a boosted tree regression method [7]. In a different study, Ata et al, proposed N2VKO as an integrative framework to predict disease genes using binary classification [8]. Moreover, Luo et al [9] and Han et al [10] predicted disease-gene associations using the joint features and deep learning classifier.…”
Section: Introductionmentioning
confidence: 99%